1974
DOI: 10.1254/jjp.24.253
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Cardiac and Pressor Responses to Propranolol of Rats and Guinea Pigs

Abstract: Abstract-Propranolol produces a sustained rise in blood pressure in the rat, but little change in the guinea pig. In order to elucidate this distinct difference, the fol lowing experiments were carried out: (a) The pressor effect of propranolol was studied while the vascular tone was changed by infusion of several vasoactive substances in the guinea pig; (b) The effect of propranolol on the isolated atria of rats and guinea pigs was also compared. Propranolol always produced a pressor action during the infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Furthermore, ;3-blockers have potential hypertensive effects, since they release catecholamines from the adrenal medulla (15), and can produce in the rat constriction of the artery through blockade of vascular ;3-receptor, for the vascular s-receptors in the rat receive rich tonic influence (32 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ;3-blockers have potential hypertensive effects, since they release catecholamines from the adrenal medulla (15), and can produce in the rat constriction of the artery through blockade of vascular ;3-receptor, for the vascular s-receptors in the rat receive rich tonic influence (32 …”
Section: Discussionmentioning
confidence: 99%
“…We assumed there is a heightened vasodilatation effect after sympathetic tonus is removed by HEX or GUA, thus PRO may raise BP in the condition of higher peripheral vasodilator tonus [20]. Compared with PRO-only, however, HEX+PRO attenuated most spectral powers, particularly with respect to LF BPV , the result indicated that uprising of efferent sympathetic discharges by reducing the afferent input of baroreflex loop is responsible for the PRO effect.…”
Section: Responses Of Precs To Promentioning
confidence: 95%
“…It is known that rat has a strong β-ADR tone in the peripheral vascular beds [20]. Our present study under PreCS, i.e., a resting condition, showed although PRO-only did not change SBP and HR, it exerts converse effects on BPV and HRV in terms of their spectral powers, they are increased in BPV and decreased for most of the HRV (VLF HRV and LF/HF HRV ), except that HF HRV was increased.…”
Section: Responses Of Precs To Promentioning
confidence: 99%